Feasibility of a Very Low Calorie Diet to Achieve a Sustainable 10% Weight Loss in Patients With Nonalcoholic Fatty Liver Disease. Issue 9 (15th September 2020) - Scragg, Jadine; Avery, Leah; Cassidy, Sophie; Taylor, Guy; Haigh, Laura; Boyle, Marie; Trenell, Michael I.; Anstee, Quentin M.; McPherson, Stuart; Hallsworth, Kate
Abstract : INTRODUCTION: Nonalcoholic fatty liver disease (NAFLD) is the most common liver condition worldwide. A weight loss goal of ≥10% is the recommended treatment for NAFLD; however, only a minority of patients achieve this level of weight reduction with standard dietary approaches. This study aimed to determine whether a very low calorie diet (VLCD) is an acceptable and feasible therapy to achieve and maintain a ≥10% weight loss in patients with clinically significant NAFLD. METHODS: Patients with clinically significant NAFLD were recruited to a VLCD (∼800 kcal/d) intervention using meal replacement products. Anthropometrics, blood tests (liver and metabolic), liver stiffness, and cardiovascular disease risk were measured at baseline, post-VLCD, and at 9-month follow-up. RESULTS: A total of 45 patients were approached of which 30 were enrolled 27 (90%) completed the VLCD intervention, and 20 (67%) were retained at 9-month follow-up. The VLCD was acceptable to patients and feasible to deliver. Intention-to-treat analysis found that 34% of patients achieved and sustained ≥10% weight loss, 51% achieved ≥7% weight loss, and 68% achieved ≥5% weight loss at 9-month follow-up. For those completing the VLCD, liver health (liver enzymes and liver stiffness), cardiovascular disease risk (blood pressure and QRISK2), metabolic health (fasting glucose, HbA1c, and insulin), and body composition significantly improved post-VLCD and was maintained at 9 months. DISCUSSION: VLCD offers a feasible treatment option for some patients with NAFLD to enable a sustainable ≥10%, weight loss, which can improve liver health, cardiovascular risk, and quality of life in those completing the intervention.